ChemInform Abstract: One‐Pot Oxidation and Rearrangement of Propargylamines and in situ Pyrazole Synthesis. Issue 7 (29th January 2015) - Chen, Jinshan; Properzi, Roberta; Uccello, Daniel P.; Young, Jennifer A.; Dushin, Russell G.; Starr, Jeremy T.
Abstract A one‐pot protocol to synthesize enaminones directly from propargylamines via oxidation and rearrangement is reported.